Code Mixing in Arabic Posts of Korean Pop Fans in TIKTOK Account - Rohmah, Alfia (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2024)
This article aims to describe the form of Arabic code mixing by Korean pop fans on Tiktok comments column. All data presented is obtained from observations in Tiktok accounts linked to the author's personal account. The observation data is in the form of sentences that contain mixed codes that appear on short videos of Korean pop fans' accounts in the form of captions, comments and sentences in videos. The data collection method used in this study is an observation method with screen capture techniques and note-taking techniques. The findings of the data are then analyzed and presented with a qualitative description explanation. From the results of the study, it appears that the mixed code contained in the Arabic uploads of Korean pop fans on Tiktok accounts is a type of mixed foreign language code or mixed code outward (outer code mixing). Based on the results of the analysis, it shows that in Arabic uploads on TikTok accounts, the Korean Pop fans use a mixture of codes by inserting elements of English and Korean in their uploads. The use of mixed codes of English elements is most predominantly found. The meaning of the mixed code consists of a denotative meaning, namely the actual meaning and the connotative meaning that refers to the distinctive meaning prevailing in the Korean Pop fan community.